School Studies Mapping Integrated Physics–Math Instructional Designs and Learning Outcomes - Maulina, Hervin; Sukamto, Ismu; Suryadinata, Nurain; Syarifuddin, Syarifuddin (Jurnal Pendidikan Matematika Universitas Lampung, 2025)
This research aims to systematically examine the application of physics-mathematics integration and its impact on learning. Through the Systematic Literature Review approach, this article analyzes 15 selected empirical research articles obtained from the Scopus and ScienceDirect databases. Article selection guided by the PRISMA method. The analysis yields five instructional design orientations that integrate physics and mathematics learning, namely problem–project integration, representation–transition integration, cross-disciplinary integration, tech–creative integration, and cognitive–affective integration. The study also found that such integrative design not only improves cognitive performance but also fosters creativity, collaboration, and confidence, which are important competencies for scientific literacy and problem-solving.